On Reliability Estimation for the Exponential Distribution Based on Monte Carlo Simulation - Salman, Abbas Najim; Taha, Taha Anwar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This Research deals with estimation the reliability function for two-parameters Exponential distribution, using different estimation methods ; Maximum likelihood, Median-First Order Statistics, Ridge Regression, Modified Thompson-Type Shrinkage and Single Stage Shrinkage methods. Comparisons among the estimators were made using Monte Carlo Simulation based on statistical indicter mean squared error (MSE) conclude that the shrinkage method perform better than the other methods